Women in arms: ¿citizen progress or feminine subjection? (2005)
This essay argues that when women enter the armed institutions they are not betraying their feminine nature nor being subjected by patriarchal logics, on the contrary they are infringing barriers constructed by a masculine vision that commandingly assigned them the domestic sphere as the ground for their fulfillment. Women’s emancipation and their road to conquest of full citizenship starts with a conscious effort to banish the feminine stereotypes–woman = maternity = intuition = sentimentalism = self-denial–that have basically served to exclude the feminine from the public world in west world democracies. A first step in the way to overcome feminine stereotypes is reached when women transgress frontiers and open up the road towards spaces before forbidden to them. If citizenship is based on principles of liberty and equality, women will conquer the highest degree of liberty as long as they, and not a vision endorsed by cultural stereotypes, freely choose the occupations and careers they wish to perform. The free development of the personality, valued today as the foundation of democracy, applies to both men and women alike. So, a democratic feminism must tend to demolish stereotypes and conquer the right to an equalitarian access and free option for women to construct their identity in any of the spheres of knowledge or social tasks.